Superthermal electron magnetosphere-ionosphere coupling in the diffuse aurora in the presence of ECH waves - Khazanov G.V.; Tripathi A.K.; Singhal R.P.; Himwich E.W.; Glocer A.; Sibeck D.G. (My University, 2025)
There are two main theories for the origin of the diffuse auroral electron precipitation: first, pitch angle scattering by electrostatic electron cyclotron harmonic (ECH) waves, and second, by whistler mode waves. Precipitating electrons initially injected from the plasma sheet to the loss cone via wave-particle interaction processes degrade in the atmosphere toward lower energies and produce secondary electrons via impact ionization of the neutral atmosphere. These secondary electrons can escape back to the magnetosphere, become trapped on closed magnetic field lines, and deposit their energy back to the inner magnetosphere. ECH and whistler mode waves can also move electrons in the opposite direction, from the loss cone into the trap zone, if the source of such electrons exists in conjugate ionospheres located at the same field lines as the trapped magnetospheric electron population. Such a situation exists in the simulation scenario of superthermal electron energy interplay in the region of diffuse aurora presented and discussed by Khazanov et al. (2014) and will be quantified in this paper by taking into account the interaction of secondary electrons with ECH waves. ©2014. American Geophysical Union. All Rights Reserved.